Mexico and its diaspora in the United States policies of emigration since 1848 - Delano, Alexandra, 1979- (Cambridge University Press, 2011)
"In the past two decades, changes in the Mexican government's policies toward the 30 million Mexican migrants living in the United States highlight the importance of the Mexican diaspora in both countries given its size, its economic power, and its growing political participation across borders. This work examines how the Mexican government's assessment of the possibilities and consequences of implementing certain emigration policies from 1848 to 2010 has been tied to changes in the bilateral relationship, which remains a key factor in Mexico's current development of strategies and policies in relation to migrants in the United States. Understanding this dynamic gives an insight into the stated and unstated objectives of Mexico's recent activism in defending migrants' rights and engaging the diaspora, the continuing linkage between Mexican migration policies and shifts in the U.S.-Mexico relationship, and the limits and possibilities for expanding shared mechanisms for the management of migration within the NAFTA framework"--